Does addition of fentanyl to morphine and local anesthetic improve the quality of spinal anesthesia? - (:unkn) unknown (MONDUZZI EDITORE, 1996)
The aim of the study was to evaluate the effect of adding intrathecal fentanyl to morphine and local anesthetic on the quality of spinal anesthesia. 24 Patients; aged 23-42 years,undergoing elective cesarean section were randomly assigned into two groups. In group I; 200 mu g morphine and 10 mg %0.5 hyperbaric bupivacaine,in group II; 200 mu g morphine,50 mu g fentanyl and 10 mg %0.5 hyperbaric bupivacaine were injected intrathecally in a total volume of 4 cc. Peroperative and postoperative pain scores (visual analogue scale) of group I were significantly higher than those of group II and postoperative first analgesic requirement was significantly earlier in group I than in group II (p<0.05). We concluded that adding fentanyl to morphine and local anesthetic intrathecally improves the quality of peroperative and postoperative analgesia.